PENYULUHAN JURNAL PENYESUAIAN DI SMK STRADA 1 - Kelvin; Rasyid, Rosmita (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2024)
Teaching assistance in an educational unit is one form of community services that can be carried out by Tarumanagara University students in the form of teaching accounting in high schools and vocational schools. This activity aims to provide accounting knowledge regarding adjusting journal that is made at the end of an accounting period. Teaching assistances is carried out in Strada 1 Vocational School through face-to-face sessions with a total of 10 meetings. There are 3 steps that is taken during the execution of teaching assistances which are preparation of teaching material, delivery of teaching materials, dan comprehension evaluation through problem solving. This activity aims to provide the Strada 1 Vocational School students with the knowledge of adjusting journals and accounting in general, while also developing Tarumanagara University students’ skills in public speaking through face-to-face teaching that will be done. The result of this activity for the Strada 1 Vocational School students is the receipt of a deeper understanding of accounting through a different teaching approach than what they are used to. The results of this activity for Tarumanagara University students are the developed skills in preparing teaching materials that is easy to understand and the development of public speaking skills in an attempt of delivering teaching materials in an engaging manner. Through teaching assistances activity, it is hoped that the Strada 1 Vocational School students will develop an interest in accounting and be equipped with the knowledge to face further education in college or challenges in the working environment.